PROCESS PARAMETER MATCHING RESEARCH ON COMPOSITE STRENGTHENING OF TITANIUM ALLOY LUG STRUCTURAL - CHANG YaNan; CAO ZengQiang; DANG ChengLong; ZHENG Guo; WEI LingFeng (Jixie qiangdu)
In order to improve the fatigue performance of the aviation lug structure,a finite element（FE） model of composite strengthening process which contains cold expansion and interference fit has been established. The influence of technological parameters on plastic deformation around hole and fatigue life of lugs has been analyzed. The residual stress test around the lug hole was carried out to verify the accuracy of the FE model. The results indicate that the plastic flow of the hole wall material with the mandrel makes the deformation of the hole wall unevenly distributed in the thickness direction. And the elastic-plastic boundary transfers to the outer side of the lug with the increase of the expansion amount. Further research shows that the maximum stress amplitude is always located at the wall of the hole and the mean stress level is the highest at the entrance when the lug structure is subjected to alternating loads. For the structure of TC4 titanium alloy lug,the increment of fatigue life can reach the maximization when the process parameters consist of 3% cold expansion and 1% interference fit.